P-086 Improvements in Patient Access and No-Show Rates Seen with an IBD Nurse Navigator. (March 2016) - Desai, Meeta; Williams, Emmanuelle; Koltun, Walter; Tinsley, Andrew; Schaefer, Marc; Falaiye, Tolulope; Stuart, August; Bobb, Anne
Abstract : Background: Nurse navigators are a recently described addition to healthcare teams that primarily focus on care-coordination. To date, their role has primarily been limited to the field of oncology due to the complexities of the disease process and potential for disjointed care. The management of inflammatory bowel disease (IBD) patients can be challenging and typically requires a multidisciplinary approach. Little is known about the impact of nurse navigators on the care of patients with IBD. Therefore, the purpose of our study was to evaluate the effect of a dedicated nurse navigator on several outcomes related to inflammatory bowel disease care. Methods: A retrospective chart review of all Penn State Inflammatory Bowel Disease Clinic patients was conducted between July 2013 (center opening) and January 2015. In March of 2014, a dedicated IBD nurse navigator (NN) was hired. We measured patient no-show rates and new patient consultation requests receiving an appointment within 21 days, before and after the introduction of a NN. We also compared the number of patients enrolled in our IBD Center Bio-Bank between both groups and evaluated patient satisfaction with the NN. Descriptive statistics as well as the Pearson's χ 2 and Student's t -tests were used in our analysis. Results: From July 2013 to February 2013, the average patient no-show rate for a physician provider in the clinic was 16.6%. After the addition of a nurse navigator the average no-show rate from March 2014 to January 2015 fell to 8.1% ( P = 0.004). Prior to the addition of a nurse navigator, 54 new patients per month were seen in under 21 days versus 74 new patients per month seen with a NN ( P = 0.035). 97% of patients reported that they were satisfied with the nurse navigator. In terms of IBD Bio-Bank patient enrollment, physicians recruited 83% of all their patients, compared to 90% with the NN. Conclusions: Inflammatory bowel disease is a complex, chronic illness that requires a significant amount of care-coordination. Nurse navigators have been utilized successfully in the field of oncology and have the potential to positively impact care for those suffering with ulcerative colitis or Crohn's disease. We found that the addition of a NN significantly improved patient access to IBD specialty care and reduced no-show rates. Patients also appear to be very satisfied with the addition of a NN to the IBD healthcare team.